Profitability, liquidity, leverage, and corporate dividend policy - Handayani, Handayani; Niandari, Nanik; Perdana, Djaja; Jati, Budhi Purwantoro (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2022)
This study examines the factors influencing dividend policy: profitability, liquidity, and leverage. The dependent variable of dividend policy is measured using the Dividend Payout Ratio (DPR). The return measures the independent variable of profitability on Equity (ROE) proxy. The independent variables of liquidity are measured using the Current Ratio (CR) proxy, and leverage is measured by the Debt-to-Equity Ratio (DER) proxy. The sampling method was purposive, and data were analyzed using multiple linear regression. The sample was manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The number of observational data used in the test totaled 221 observations. This research shows that profitability positively affects the dividend payout ratio, and other variables, namely liquidity, and leverage, do not affect dividend policy. The research results are expected to add to the research literature on the factors influencing dividend policy